Human microsomal carbonyl reducing enzymes in the metabolism of xenobiotics: well-known and promising members of the SDR superfamily - Skarydová, Lucie; Wsól, Vladimír (Drug metabolism reviews, 2012)
The best known, most widely studied enzyme system in phase I biotransformation is cytochrome P450 (CYP), which participates in the metabolism of roughly 9 of 10 drugs in use today. The main biotransformation isoforms of CYP are associated with the membrane of the endoplasmatic reticulum (ER). Other enzymes that are also active in phase I biotransformation are carbonyl reducing enzymes. Much is known about the role of cytosolic forms of carbonyl reducing enzymes in the metabolism of xenobiotics, but their microsomal forms have been mostly poorly studied. The only well-known microsomal carbonyl reducing enzyme taking part in the biotransformation of xenobiotics is 11β-hydroxysteroid dehydrogenase 1, a member of the short-chain dehydrogenase/reductase superfamily. Physiological roles of microsomal carbonyl reducing enzymes are better known than their participation in the metabolism of xenobiotics. This review is a summary of the fragmentary information known about the roles of the microsomal forms. Besides 11β-hydroxysteroid dehydrogenase 1, it has been reported, so far, that retinol dehydrogenase 12 participates only in the detoxification of unsaturated aldehydes formed upon oxidative stress. Another promising group of microsomal biotransformation carbonyl reducing enzymes are some members of 17β-hydroxysteroid dehydrogenases. Generally, it is clear that this area is, overall, quite unexplored, but carbonyl reducing enzymes located in the ER have proven very interesting. The study of these enzymes could shed new light on the metabolism of several clinically used drugs or they could become an important target in connection with some diseases.
Keywords: Biotransformation; 17-hydroxysteroidní dehydrogenasy; Humans; Catalysis; Substrate Specificity; Carboxylic Acids; mikrozomy; oxidace-redukce; alkoholoxidoreduktasy; 11-beta-hydroxysteroiddehydrogenasa typ 1; kyseliny karboxylové; lidé; Xenobiotics; zvířata; molekulární struktura; Molecular Structure; Microsomes; 11-beta-Hydroxysteroid Dehydrogenase Type 1; Endoplasmic Reticulum; substrátová specifita; xenobiotika; Oxidation-Reduction; biotransformace; endoplazmatické retikulum; Animals; 17-Hydroxysteroid Dehydrogenases; Alcohol Oxidoreductases; katalýza